Organic Waste Management Based on Eco-Enzymes and Maggots as a Sustainable Solution for the Environment - Purwanta; Faozi, Arif Rahman; Atha, Assyfa (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Organic waste is becoming a more significant environmental problem since it contributes significantly to landfill degradation. Organic waste is a common type of garbage produced. Managing waste is a severe problem, especially in urban areas like Puntukdoro village, Plaosan sub-district, Magetan regency, East Java. Our region’s lack of knowledge and awareness of organic waste management is still significant. This community service initiative used sustainable organic waste management techniques to solve this problem. The project highlighted the value of community engagement and the possible advantages of managing organic waste, such as less garbage going to landfills, compost rich in nutrients for gardening, and increased environmental sustainability. The project’s results include participant satisfaction, information acquired, and the practical application of waste management techniques. We have opted for an eco-enzyme and macro-organism (maggot) waste treatment system, which is simple enough for anyone to implement at home—through workshops, demonstrations, and hands-on training, the Community Empowerment Learning Community Service Lecture (KKN-PPM UGM) second-period conducted the study (June - August 2024). Participants learned about composting techniques, management, and how to make creative inventions because the waste management system we chose has many benefits in any field, especially in agriculture. Forty participants participated in the program’s performance activities, which promoted gradual social change by developing psychomotor skills, affective awareness embedding, cognitive understanding, and a conative behavioural change spirit. In general, this policy has been successful in enhancing society. The accomplishment of the Sustainable Development Goals (SDGs) for environmental preservation is made possible by the program’s success.